2007
DOI: 10.2174/138945007780362746
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Solid Organ Transplantation

Abstract: Approximately seventy patients undergo solid organ transplantation (SOT) every day in the United States. Sepsis remains the first or second most common cause of death in transplant recipients, depending on the allograft type. The rapid diagnosis and treatment of sepsis is critical to ensure improved survival outcome in this special patient population. However, these patients frequently lack the classic systemic inflammatory response syndrome (SIRS), commonly seen in the immunocompetent patients. In order to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 79 publications
0
30
0
4
Order By: Relevance
“…Sepsis is the second leading cause of death among abdominal transplant patients despite advances in immunosuppression, surgical techniques, and antibiotic prophylaxis (1). The mortality risk associated with bacteremia within the solid organ transplant population is reported to be as high as 70%, depending on the organism, site of infection, and timing of occurrence post transplantation (2).…”
mentioning
confidence: 99%
“…Sepsis is the second leading cause of death among abdominal transplant patients despite advances in immunosuppression, surgical techniques, and antibiotic prophylaxis (1). The mortality risk associated with bacteremia within the solid organ transplant population is reported to be as high as 70%, depending on the organism, site of infection, and timing of occurrence post transplantation (2).…”
mentioning
confidence: 99%
“…Importantly, high lab-MELD scores and a critical health status may promote early infectious complications after LT. Kim et al [40] showed that the predominating infectious complication after LT is bacterially related, especially during the 1st month after LT (40% of bacterial infections), and that the infection-related mortality in all LT patients is 53% [10,15,41] . Patients develop SIRS and sepsis and do require less immunosuppression [16] . Our data indicate a lower incidence of infectious complications in the 'bottom-up'/'on demand' group.…”
Section: Discussionmentioning
confidence: 99%
“…This disturbed regulation increases the susceptibility for a broad range of normal and opportunistic infections [13] . Therefore, patients with high lab-MELD scores should hypothetically require a rather low amount of immunosuppressive drugs during the first days and weeks after transplantation, while they are in a state of SIRS (systemic inflammatory response syndrome)-like state [16,17] .…”
mentioning
confidence: 99%
“…All drugs currently used for immunosuppression cause significant clinical side effects. Besides their well-known intrinsic toxicities (e.g., neurotoxicity of tacrolimus and renal toxicity of ciclosporin [3-5]), they also increase the risk for cancer and opportunistic infections [6-11]. The long-term overall success of liver transplantation is frequently determined by complications related to immunosuppressive drug therapy.…”
Section: Introductionmentioning
confidence: 99%